SISTEM PENDINGIN PANEL SURYA OTOMATIS UNTUK MENGKATKAN DAYA KELUARAN PANEL SURYA - Prima Dewi, Riyani (Fakultas Teknik Universitas Muria Kudus, 2023)
Solar panels are the main component of solar power plant. In the Solar panels, conversion of solar energy into electrical energy are done. The results of the electrical energy produced by solar panels depend on the amount of solar intensity received by the solar panels. In addition, the working temperature of solar panels is also crucial. The ideal solar panel temperature is 25 C, which means that the solar panel will work optimally at that condition. When the temperature rises, the solar cell performance will decrease. This study aims to design a solar panel cooling system with active and passive methods using a way of flowing water over the surface of the solar panel and adding wet coconut coir on the back of the solar panel. The purpose of providing this treatment is to keep the surface temperature of the solar panel from overheating. This study uses a 100 WP solar panel and the results obtained that the average power generated is 69 W with an average voltage value of 15.47 V and an average current of 4.5 A. The performance 100 WP solar panels increased 24% of the reference solar panels being compared